Reasons behind Dropping out of Slum Children from Non-formal School in Dhaka - Marzia Khatan Smita; Md. Fajlay Rabbi; Shoeab Mohammad (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
In South Asia, numerous slum children were deprived of education upon several socio-economic grounds, and many children still dropout of non-formal schools despite receiving free non-formal education. This study aims to explore the reasons for dropping out of non-formal schools and the socio-demographic situation of slum children in Dhaka City. Fifty non-formal dropout slum children were selected conveniently as participants employing a mixed research design. A semi-structured schedule of questionnaire and interview was used as instruments for collecting data. Both qualitative and quantitative data were collected simultaneously to explore the slum children's dropout situation. Twelve reasons of their dropout have been reported. In addition to explaining the reasons for their dropping out, two frameworks were presented in detail. Most slum non-formal students dropped out of their schools for the pulling out factors and reasons related to household. Recommendations for reducing slum children's school dropout and persuasive strategies for future work in this field have been addressed. Keywords: Non-formal School, Dropout, Slum Children, Non-formal Education.